2017
DOI: 10.1002/ajp.22660
|View full text |Cite
|
Sign up to set email alerts
|

How do rivers, geographic distance, and dispersal behavior influence genetic structure in two sympatric New World monkeys?

Abstract: Dispersal, one of the major factors affecting the gene flow between populations, shapes the spatial distribution of genetic diversity within species. Alouatta macconnelli and Saguinus midas are two Neotropical monkey species that sympatrically inhabit the Guiana shield in northern Amazonia and are likely to differ in their dispersal behavior and vagility. We took advantage of their sympatry to investigate, over a fine geographical scale (∼50 km long), the relationship between spatial genetic structure, on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 84 publications
(123 reference statements)
0
21
0
Order By: Relevance
“…Generally, large rivers can act as effective barrier to gene flow in various taxonomic groups, such as mammals (e.g., Canis lupus , Carmichael, Nagy, Larter, & Strobeck, ; Pan paniscus , Eriksson, Hohmann, Boesch, & Vigilant, ), reptiles (e.g., Gymnodactylus darwinii complex, Pellegrino et al., ) and even amphibians (e.g., R. kukunoris , Zhao et al., ; S. boulengeri , Li et al., ; Ichthyophis bannanicus , Wang et al., ; Microhyla fissipes complex, Yuan et al., and N. pleskei , Zhou et al., ). However, rivers cannot limit gene flow in those species capable of swimming (e.g., Lontra canadensis , Blundell, Ben‐David, Groves, Bowyer, & Geffen, ; Ursus americanus , Cushman et al., ) or with high mobility ( Saguinus midas and Alouatta macconnelli , Lecompte, Bouanani, de Thoisy, & Crouau‐Roy, ). For deer species, such as O. virginianus (Robinson et al., ), rivers were often considered as an important geographical barrier.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, large rivers can act as effective barrier to gene flow in various taxonomic groups, such as mammals (e.g., Canis lupus , Carmichael, Nagy, Larter, & Strobeck, ; Pan paniscus , Eriksson, Hohmann, Boesch, & Vigilant, ), reptiles (e.g., Gymnodactylus darwinii complex, Pellegrino et al., ) and even amphibians (e.g., R. kukunoris , Zhao et al., ; S. boulengeri , Li et al., ; Ichthyophis bannanicus , Wang et al., ; Microhyla fissipes complex, Yuan et al., and N. pleskei , Zhou et al., ). However, rivers cannot limit gene flow in those species capable of swimming (e.g., Lontra canadensis , Blundell, Ben‐David, Groves, Bowyer, & Geffen, ; Ursus americanus , Cushman et al., ) or with high mobility ( Saguinus midas and Alouatta macconnelli , Lecompte, Bouanani, de Thoisy, & Crouau‐Roy, ). For deer species, such as O. virginianus (Robinson et al., ), rivers were often considered as an important geographical barrier.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, active dispersal of species from the Amazon basin could maintain large sink populations, and such dispersal could be evolutionarily stable, developing a nested structure of species richness. Therefore, we emphasize the importance of dispersal ability and extinction processes in generating the source–sink dynamics and the observed richness pattern, especially considering that some species can be very vagile and have a wide range of distribution that covers areas with low and high available energy ( Ayres & Clutton-Brock, 1992 ; Jablonski, Roy & Valentine, 2006 ; Lecompte et al, 2017 ). Also, our results show that in the Neotropics there is higher species co-occurrence than expected by chance, and the significant nestedness score indicates that interspecific competition may be not a factor that determines the nature of the species richness pattern.…”
Section: Discussionmentioning
confidence: 99%
“… Ayres & Clutton-Brock (1992) first suggested that Amazonian rivers are effective barriers to primate species dispersal, largely related to their width, seasonal and annual stability, rate of flow, and the ability of species to cross these environmental barriers. However, despite the long-term stability of some of these watercourses, recent studies found no evidence that rivers acts as an effective barrier ( Boubli et al, 2015 ; Lecompte et al, 2017 ). Thus, from a macroecological perspective, these lower and upper boundaries are the most important feature of the relationships between species richness and climatic variables, because they appear to represent a limit to the number of species for a given geographic area and a given combination of habitat properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under this scenario, local resource competition and cooperation should have a minor influence on sex allocation. In well‐studied populations, however, related individuals often live in the same groups and kinship relationships affect social relationships (e.g., Cristóbal Azkarate et al, ; Dias et al, ; Lecompte, Bouanani, de Thoisy, & Crouau‐Roy, ; Nidiffer & Cortés‐Ortiz, ; Pope, , ; Rudran & Fernández‐Duque, ; Van Belle, Estrada, & Di Fiore, ; Van Belle, Estrada, Strier, & Di Fiore, ). For instance, in both black and ursine howler monkeys, females actively recruit females from their own matrilines and force the daughters of other females to emigrate (Crockett, ; Horwich, Brockett, James, & Jones, ; Rumiz, ).…”
Section: Discussionmentioning
confidence: 99%